PELATIHAN PENGKAFANAN JENAZAH DESA SAMBIRATA - Wulandari, Inayah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2024)
Funeral care is an important part of Islamic law that is often carried out by people only based on habits, without a deep understanding of sharia guidance. This lack of knowledge often causes the care of the body not to be in accordance with Islamic teachings. To overcome this problem, the UNUGHA Cilacap Community Service Program (KKN) carried out a training on shrouding bodies in Sambirata Village, Cilongok District, Banyumas Regency. This training aims to improve the community's understanding and skills in the procedures for managing bodies in accordance with the guidance of the Prophet PBUH. The methods used include material presentation and direct practice, with discussion and demonstration sessions. The results of the training showed high enthusiasm from the participants, as well as a better understanding of the procedures for taking care of the corpse. This program is expected to have a positive impact and increase public awareness about the importance of caring for bodies in accordance with Islamic law.